2009
DOI: 10.1590/s1415-47572009005000068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L1-ORF2 fragments on green fluorescent protein gene expression

Abstract: The retrotransposon known as long interspersed nuclear element-1 (L1) is 6 kb long, although most L1s in mammalian and other eukaryotic cells are truncated. L1 contains two open reading frames, ORF1 and ORF2, that code for an RNA-binding protein and a protein with endonuclease and reverse transcriptase activities, respectively. In this work, we examined the effects of full length L1-ORF2 and ORF2 fragments on green fluorescent protein gene (GFP) expression when inserted into the pEGFP-C1 vector downstream of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…However, when retrotransposons integrate, they may also impact transcriptional regulation [17] , [19] , [20] and/or chromatin structure [21] , [22] . For example, Wang et al showed that different fragments of the L1-ORF2 modulated transcription termination of upstream GFP expression [23] , demonstrating functional impact of the L1 sequence on gene transcription without a direct disruption of coding sequence. The functional consequences of RT retrotransposition are not always deleterious, however, and in some instances they have led to the evolution of mammalian-specific [24] and human-specific traits [25] .…”
Section: Introductionmentioning
confidence: 99%
“…However, when retrotransposons integrate, they may also impact transcriptional regulation [17] , [19] , [20] and/or chromatin structure [21] , [22] . For example, Wang et al showed that different fragments of the L1-ORF2 modulated transcription termination of upstream GFP expression [23] , demonstrating functional impact of the L1 sequence on gene transcription without a direct disruption of coding sequence. The functional consequences of RT retrotransposition are not always deleterious, however, and in some instances they have led to the evolution of mammalian-specific [24] and human-specific traits [25] .…”
Section: Introductionmentioning
confidence: 99%
“…Since XCI is a mechanism of gene dosage compensation by regulating gene expression [31][32][33][34] and our previous studies proved that L1s and Alus played a role in regulating gene expression [35][36], we speculated that these two repetitive sequences (L1 and Alu) may be involved in the process of XCI by regulating gene expression.…”
Section: Introductionmentioning
confidence: 90%
“…The pAlu14 and pORF2 expression vectors were constructed as described elsewhere ( Wang et al , 2009a , b ) by inserting 14 head-to-tail tandem Alu (283 bp) elements or an ORF2 (3825 bp) downstream of the GFP gene in the pEGFP-C1 vector.…”
Section: Methodsmentioning
confidence: 99%
“…Alu elements were initially considered to have no role in gene stability and expression, but recent work has shown that these elements can extensively influence gene expression. In previous work, we have shown that Alu tandem repeats and Line-1 - ORF2 ( ORF2 ) inhibited green fluorescent protein (GFP) gene expression when inserted downstream of this gene in the pEGFP-C1 vector ( Wang et al , 2009a , b ). Downstream noncoding gene sequences are highly structured and contain important regulatory elements such as 3′ UTRs, transcription termination signals ( Andreassi and Riccio, 2009 ) and enhancers ( Mao et al , 2010 ).…”
Section: Introductionmentioning
confidence: 99%